Pengaruh Contextual Teaching and Learning (CTL) terhadap Prestasi Siswa pada Bidang Studi PAI di SDIT Insantama Banjar - Fajar Farhan Hikam; Salma Karima (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2020)
The purpose of this study was to determine how much influence the Contextual Teaching and Learning (CTL) learning method has on student achievement in the field of Islamic Religious Education (PAI), this implementation was carried out at SDIT Insantama Banjar. With this it is identified that the Contextual Teaching and Learning (CTL) learning method is named as the X variable while the PAI learning achievement is named as the Y variable. This research is a correlation study with a quantitative approach with a population of 23 people all of which are used as research samples. Based on data processing, that there is a significant effect of the CTL learning method on student achievement with the regression equation Y = 10,412 + 1,705 X. The results of the correlation coefficient or the relationship turned out to show a significant relationship between the two variables studied, the coefficient and correlation values obtained Contextual Teaching and Learning (CTL) learning methods with learning achievements in the field of Islamic Religious Education (PAI). Contextual Teaching and Learning (CTL) learning methods have a strong influence on student achievement.